2013
DOI: 10.3109/02813432.2013.854445
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in managing elderly people with diabetes in primary care settings in Norway

Abstract: ObjectiveTo explore the experiences and clinical challenges that nurses and nursing assistants face when providing high-quality diabetes-specific management and care for elderly people with diabetes in primary care settings.DesignFocus-group interviews.Subjects and settingSixteen health care professionals: 12 registered nurses and four nursing assistants from nursing homes (10), district nursing service (5), and a service unit (1) were recruited by municipal managers who had local knowledge and knew the workfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 24 publications
0
22
0
3
Order By: Relevance
“…Six studies reported both qualitative and quantitative data [313233343536], ten qualitative only [27293738394041424344], and three quantitative only [283045]. The numbers and characteristics of the participants involved in the included publications are given in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies reported both qualitative and quantitative data [313233343536], ten qualitative only [27293738394041424344], and three quantitative only [283045]. The numbers and characteristics of the participants involved in the included publications are given in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that although GPs reported unsatisfactory collaboration with nursing homes [303742], HCNs [27313745] and physiotherapists [29], they lacked the time, experience and training to engage in improving their practice [3031]. Attending to the intrinsic capacities, barriers, needs and interdependencies of primary care requires a systemic approach in which local health and social care managers share responsibility with professionals and lay people in boosting clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A atitude em relação à doença pode ou não ser influenciada pelo conhecimento insatisfatório sobre ela, bem como pelo significado que o indivíduo atribui à condição crônica (12,(20)(21) . Há que se considerar que a motivação e as atitudes do paciente frente à doença não são cristalizadas, pois são influenciadas por componentes cognitivos, motivacionais, emocionais e de conhecimento sobre a doença (22) .…”
Section: Discussionunclassified
“…A gestão da condição crônica pelo próprio indivíduo é essencial, pois pode existir discrepância entre o conhecimento que os profissionais consideram importante para a realização do cuidado e a capacidade de produzi-los (20) .…”
Section: Referênciasunclassified
“…Another study explored the experiences and clinical challenges that nurses and nursing assistants face in municipal health service in primary care settings when providing high-quality diabetes care for elderly people [36]. It found that good communication with more experienced health care professionals and access to the right information is particularly important to the staff’s confidence and autonomy in order to make clinical decisions, and that the lack of it was contributory to their experience of not being able to care adequately for the patients.…”
Section: Discussionmentioning
confidence: 99%